The Role of Angiopoietin-2 Gene Mutation on Clinical Severity of Dengue Disease in Children - Akmal, Mayetti; Amirah Zatil Izzah; Jamsari; Eriyati Darwin; Dadang Hudaya Somasetia (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: In general, angiopoietin-2 levels are increased concomitantly with dengue clinical severity. AIM: This research aims to determine the role of mutation on angiopoietin-2 on dengue clinical severity. METHODS: A cross-sectional study of 108 children with dengue disease grouped by severity. Angiopoietin-2 level was examined by enzyme-linked immunosorbent assay. Polymerase chain reaction and double nucleic acid sequencing are using 2 Exon 4-F primers. RESULTS: Angiopoietin-2 levels on rs7834131 mutant are higher in dengue fever (p < 0.05) and dengue hemorrhage fever group than non-mutant, while on dengue shock syndrome, it is lower than non-mutant. CONCLUSION: Angiopoietin-2 mutation on rs7834131 might have a protective effect on dengue disease severity.